RANDOM FORCE MODELING AND VIBRATION ANALYSIS OF FIXED ABRASIVE WIRE SAW - JI LeiLei; TANG AoFei; GUO XiaoLing; CUI FangYuan (Jixie qiangdu)
The main approach to cut the brittle-hard material is the use of the fixed abrasive wire saw at present. The vibration of the wire saw is inevitable during the cutting process for the reason of its flexibility. The main vibration patterns include the incentive of abrasive grains to the wire saw and vibrations transmitted by the machine itself. For the sake of investigating the effect of abrasive grains on the vibration of wire saws during cutting process, based on the oscillation theory of the string, the vibration equations of the wire saw in the case of a damped axially uniform motion were constructed and together with an analysis of the force in the wire saw during the process of cutting. The normal random force model, which has an important influence on the lateral vibration of the wire saw,was further established and an analysis of linear vibration of the wire saw in the small offset state was conducted. Based on the cutting experiment of WXD170 reciprocating diamond wire sawing machine, the validity of the normal random force model is verified. The results show that the simulation of the vibration model can accurately predict the vibration during the sawing process.